2021
DOI: 10.1111/os.12887
|View full text |Cite
|
Sign up to set email alerts
|

Novel Design of the Chimeric Deep Inferior Epigastric Artery Perforator Flap that Provides for Three‐Dimensional Reconstruction of Composite Tissue Defects of the Heel in Children

Abstract: Objective The aim of the present study was to report a novel design of the chimeric deep inferior epigastric artery perforator flap (DIEP) to achieve dead space filling, Achilles tendon bridging, and skin resurfacing simultaneously with minimal donor‐site morbidity. Methods From September 2012 to May 2016, a retrospective study was carried out on six pediatric patients with composite soft tissue defects of the heel that were repaired with the chimeric DIEP flap. The chimeric flap design included a flap of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…One‐hundred‐fourteen full‐text articles were assessed for eligibility. Seventy of these were excluded and the remaining forty‐four have been divided based on type of technique reported: local flaps (Liu et al, 2014; Masquelet et al, 1992; Nguyen et al, 2023; Ring et al, 2016; Woo et al, 2022; Zelken & Lin, 2016), free flaps (Akdag et al, 2018; Battiston et al, 2015; Calotta et al, 2018; Cherubino et al, 2020; Colterjohn et al, 1997; He et al, 2022; Kim et al, 2021; Kozusko et al, 2019; Medina 3rd et al, 2014; Musharafieh et al, 2001; Namdar et al, 2010; Nosrati et al, 2012; Periasamy et al, 2023; Sailon et al, 2009; Sayyed et al, 2022; Ulusal et al, 2005; Yu et al, 2021), perforator flaps (D'Arpa et al, 2014; Ellabban et al, 2020; Khan et al, 2020; Kwon et al, 2021; Lee et al, 2017; Li et al, 2021; Lin et al, 2021; Pignatti et al, 2011; Ring et al, 2016; Toia et al, 2017), skin grafts (Asif et al, 2018; Kang et al, 2019; Leclère & Casoli, 2016; Schneider et al, 2009; Shimizu & Kishi, 2012) and free bone (fibula) or osteocutaneous transfer (de Boer et al, 1990; El‐Gammal et al, 2002; Han et al, 1992; Toma et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One‐hundred‐fourteen full‐text articles were assessed for eligibility. Seventy of these were excluded and the remaining forty‐four have been divided based on type of technique reported: local flaps (Liu et al, 2014; Masquelet et al, 1992; Nguyen et al, 2023; Ring et al, 2016; Woo et al, 2022; Zelken & Lin, 2016), free flaps (Akdag et al, 2018; Battiston et al, 2015; Calotta et al, 2018; Cherubino et al, 2020; Colterjohn et al, 1997; He et al, 2022; Kim et al, 2021; Kozusko et al, 2019; Medina 3rd et al, 2014; Musharafieh et al, 2001; Namdar et al, 2010; Nosrati et al, 2012; Periasamy et al, 2023; Sailon et al, 2009; Sayyed et al, 2022; Ulusal et al, 2005; Yu et al, 2021), perforator flaps (D'Arpa et al, 2014; Ellabban et al, 2020; Khan et al, 2020; Kwon et al, 2021; Lee et al, 2017; Li et al, 2021; Lin et al, 2021; Pignatti et al, 2011; Ring et al, 2016; Toia et al, 2017), skin grafts (Asif et al, 2018; Kang et al, 2019; Leclère & Casoli, 2016; Schneider et al, 2009; Shimizu & Kishi, 2012) and free bone (fibula) or osteocutaneous transfer (de Boer et al, 1990; El‐Gammal et al, 2002; Han et al, 1992; Toma et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The vertical deep inferior epigastric perforator flap has been also successfully used for selected lower extremity soft tissue reconstructions (Akdag et al, 2018). Along with the latissimus dorsi, the RAF is commonly used in microsurgical reconstruction for pediatric patients (Yu et al, 2021). The muscle component of the flap is ideal for filling dead space, a crucial factor in lower extremity reconstruction, while the cutaneous component provides coverage.…”
Section: Rectus Abdominis Flapmentioning
confidence: 99%
“…16 However, the traditional pedicled musculocutaneous flap lacks flexibility because of a close connection between the skin flap and muscle component, making it unsuitable for repairing the complex defect where the dead space and the skin defect are at different locations. 9,17 The SGAP flap is commonly used for repairing defects in the sacrococcygeal region. 1 Nevertheless, the perforator flap cannot provide abundant bulk to kill the dead space effectively because of the lack of muscle components.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review and meta-analysis identified gluteal-based and vertical rectus abdominis musculocutaneous flaps as the 2 most common options for soft tissue reconstruction after sacrectomy 16 . However, the traditional pedicled musculocutaneous flap lacks flexibility because of a close connection between the skin flap and muscle component, making it unsuitable for repairing the complex defect where the dead space and the skin defect are at different locations 9,17 . The SGAP flap is commonly used for repairing defects in the sacrococcygeal region 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, skin and deep tissue defects can be repaired simultaneously by anastomosing a group of blood vessels. In addition, the latissimus dorsi muscle has an abundant blood supply and a good capacity to resist infection [ 30 ]. Additionally, the muscle paddle can be accurately harvested according to the size of the dead space, which not only improves the quality of recipient site repair but also preserves the integrity of the latissimus dorsi to the greatest extent possible.…”
Section: Discussionmentioning
confidence: 99%